Mobilising stories about cultural beliefs and practices on traditional foods to contextualise the topic on nutrition in a Grade 6 township class - Nuntsu, Sipho Nimrod (Rhodes University, Faculty of Education, Department of Education)
The South African Curriculum Assessment and Policy Statement (CAPS) document stipulates that science teachers should integrate indigenous knowledge (IK) into their science teaching. The rationale for this is to contextualise the content and make science accessible and relevant to learners. Despite these ideals, however, CAPS seems to be silent on how science teachers should go about doing this. Instead, it assumes that all teachers know how to integrate IK in their science teaching. As a result, many teachers are still not sure of how to integrate IK into their science classrooms. Such rhetoric and tension between curriculum formulation and implementation triggered my interest to do a study on how to mobilise stories about cultural beliefs and practices of traditional foods to mediate learning of nutrition in a Grade 6 Natural Sciences township class. The study was underpinned by an interprevist paradigm complemented with an Ubuntu paradigm to enhance explanations. Within these paradigms, a qualitative case study research design was adopted. It was conducted at Mdoko Primary school (pseudonym) in a semi-urban community in the Amathole West district of the Eastern Cape. The participants were 34 Grade 6 learners (15 boys and 19 girls), a Grade 6 Natural Sciences teacher who was my critical friend, and two expert community members. To generate data, I used a focus group discussion, group activities, classroom observations, and learners' reflective journals. Vygotsky's socio-cultural theory and Ogunniyi's Contiguity Argumentation Theory (CAT) were used as theoretical and analytical frameworks, respectively. A thematic approach to data analysis was employed. That is, data were analysed inductively to identify sub-themes and subsequently similar sub-themes were grouped together to form themes. The two expert community members' presentations equipped my learners with stories on cultural beliefs and practices that were used in the olden days (past) and how such stories are used in our days (present). For instance, the findings of this study revealed that women during menstruation must not drink amasi as it is believed that it would prolong the menstruation time. The findings also revealed that eating of amaqanda and inside meat by youths should be minimised as it is believed that it can stimulate their sex hormones. It also revealed that there is no relevance to science that men eating imifino would be weak among other men who do not eat them. The implications for this study is that science teachers should make some efforts to integrate IK in their teaching to make science accessible and relevant to their learners. To achieve this, the study thus recommends that science teachers should find ways of tapping into the cultural heritage and wisdom that is possessed by the expert community members to enable learners to cross the bridge from home to school.
Keywords: Culturally relevant pedagogy -- South Africa; Science-- Study and teaching (Elementary) -- South Africa; Nutrition-- Study and teaching (Elementary) -- South Africa; Traditional ecological knowledge -- South Africa; Storytelling; Reasoning; Contiguity Argumentation Theory (CAT); South African Curriculum Assessment and Policy Statement (CAPS); Socio-cultural theory